2021
DOI: 10.1021/acssuschemeng.0c08643
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Sustainable Ammonia-Based Food–Energy–Water Systems with Nitrogen Management

Abstract: As the basis for virtually any form of nitrogen fertilizers, ammonia plays a vital role in agriculture; in addition, there has been an increased interest in its use as a carbon-free energy carrier. However, ammonia is also associated with two major environmental concerns: CO 2 emissions from the conventional production process and nitrogen pollution from the excessive use of ammoniabased fertilizers. To mitigate these environmental impacts, we develop an optimization framework for the design of a sustainable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In this techno-economic analysis, we aim to determine optimal designs of green offshore ammonia systems in various scenarios and gain insights into the main contributing factors with respect to the costs of such systems. To this end, we apply a superstructure-based design optimization approach adopted from our previous work . It selects the best configuration comprising a set of given design options while simultaneously optimizing the operational schedule under the chosen design.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this techno-economic analysis, we aim to determine optimal designs of green offshore ammonia systems in various scenarios and gain insights into the main contributing factors with respect to the costs of such systems. To this end, we apply a superstructure-based design optimization approach adopted from our previous work . It selects the best configuration comprising a set of given design options while simultaneously optimizing the operational schedule under the chosen design.…”
Section: Methodsmentioning
confidence: 99%
“…Considering this level of detail in modeling the plant operations is particularly important due to the strong intermittency in wind availability. Several existing studies have shown that failing to account for such dynamics can lead to unsound design decisions. , For the sake of conciseness, we keep the description of the model brief; for more details, we refer to the reader to our previous work from which the formulation is adopted …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23] Therefore, this work primarily focuses on emerging electrochemical technologies that can be combined to convert nitrogenous-waste to value added products, such as ammonia and other fertilizers, thereby partially offsetting the GWP and financial cost associated with ammonia produced by the Haber-Bosch process. 24,25 Our study examines a hypothetical three-part NCC system based on the three technologies listed above that have been demonstrated individually on the lab-scale. A schematic of this hypothetical system is presented in Figure 2, where the Haber-Bosch system boundaries are shown independently as well as supplemented by an NCC system.…”
mentioning
confidence: 99%